From Quest to Conquer: Traversing General Education at a Diverse Alaskan University to Integrate and Assess Transferable Information Literacy Skills in Foundational Courses - Bjartmarsdóttir, Anna; Mole, Deborah L. (Nordic Journal of Information Literacy in Higher Education, 2016)
The University of Alaska Anchorage (UAA) is an open enrollment university that offers vocational, academic, and professional degrees in a northern region. UAA serves a culturally and demographically diverse population. Given this diversity, students display varying levels of information literacy (IL) competencies. Library Professors Anna Bjartmarsdóttir and Deborah Mole partner with faculty teaching composition and communication courses to create increasingly sophisticated and transferable IL learning opportunities. Strategies include: assessing students’ IL competencies; creating engaging activities; integrating IL throughout the semester; developing reflection opportunities to reinforce IL skills. UAA librarians, partnered with faculty, integrate and scaffold IL activities in foundational GE courses to develop increasingly sophisticated, transferable IL skills and knowledge practices. From team-based learning application exercises to workshops for teaching assistants, students learn how creativity partnered with initiative has helped to integrate transferable IL skill education at this diverse arctic university.